Vacuolar accumulation and colocalization is not a proper criterion for cytoplasmic soluble proteins undergoing selective autophagy. (3rd October 2021) - Yu, Jingfang; Zhou, Jun
ABSTRACT: Autophagy is an important cytoprotective process that mediates degradation of dysfunctional or unnecessary cellular components. In the process of autophagy, a double-membrane organelle termed the autophagosome is formed to sequestrate portions of cytoplasm and subsequently delivered into lysosome or vacuole for degradation. The accumulation of autophagic bodies in the vacuoles after treatment with concanamycin A (ConcA) is a widely used protocol for monitoring the occurrence of autophagy in plants. Here, it was found that the cytoplasmic soluble GFP was accumulated in vacuoles upon ConcA treatment. Importantly, the GFP signal showed good colocalization with the autophagic marker mCherry-ATG8f in vacuoles based on two commonly used methods, the Pearson-Spearman correlation colocalization analysis and the plot profile analysis. Further results showed that the free GFP did not interact with ATG8s. Thus, analysis of accumulation and colocalization only in vacuoles is not a trustworthy way to judge whether degradation of cytoplasmic protein is dependent on the selective autophagy pathway in plants. In this short perspective, we propose several primary steps to distinguish that the cytoplasmic proteins are degraded by selective or bulk autophagy, hoping they could contribute to identify and clarify the selective autophagic cargos and receptors in plants.